Array Microcell Method (AMCM) for Serial Electroanalysis. Issue 5 (24th January 2020) - Alden, Sasha E.; Siepser, Natasha P.; Patterson, Jacqueline A.; Jagdale, Gargi S.; Choi, Myunghoon; Baker, Lane A.
Abstract: We describe a method for electrochemical measurement and synthesis based on the combination of a mobile micropipette and a microelectrode array, which we term the array microcell method (AMCM). AMCM has the ability to address single electrodes within a microelectrode array (MEA) and provides a simple, low‐cost format to enable versatile electrochemical measurements. In AMCM, a droplet at the tip of a movable micropipette (inner diameter of 50 μm) functions as an electrochemical cell, in which the electrode area is defined by a microelectrode of the array. We also report carbon MEAs that are well suited for AMCM and are fabricated from pyrolyzed photoresist films (PPFs). PPF‐MEAs with nominal electrode diameters of 5.5 μm are characterized by AMCM, standard macroscale electrochemical methods, and finite element modeling. The versatility of AMCM is demonstrated by measurement of single Pt microparticles and by electrodeposition of shape‐controlled Pt nanoparticles. Abstract : Method in the madness : The array microcontact method (AMCM) is described, which provides a simple but powerful tool to employ microelectrode arrays for electrochemical and materials studies.